2020
DOI: 10.1103/physrevb.101.094107
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order topological phases in a spring-mass model on a breathing kagome lattice

Abstract: We propose a realization of higher-order topological phases in a spring-mass model with a breathing kagome structure. To demonstrate the existence of the higher-order topological phases, we characterize the topological properties with the Z3 Berry phase, and show that the corner states appear under the fixed boundary condition. Moreover, we suggest that the corner states can be detected experimentally through a forced vibration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…1(k)]. The chain consists of N 1 unit cells with the rotors as well as the fixed pivots labeled A n 1 and B n 1 (1 n 1 N 1 ) and is subjected to fixed boundary conditions [111,112] at rotors B 0 and A N 1 +1 . The equilibrium configuration is that the A rotors (B rotors) make an (1,15) with ω ext = 1.13 and F = 10 −10 .…”
Section: A Non-hermitian Topological Mechanics In the 1d Rotor Chainmentioning
confidence: 99%
“…1(k)]. The chain consists of N 1 unit cells with the rotors as well as the fixed pivots labeled A n 1 and B n 1 (1 n 1 N 1 ) and is subjected to fixed boundary conditions [111,112] at rotors B 0 and A N 1 +1 . The equilibrium configuration is that the A rotors (B rotors) make an (1,15) with ω ext = 1.13 and F = 10 −10 .…”
Section: A Non-hermitian Topological Mechanics In the 1d Rotor Chainmentioning
confidence: 99%
“…We have demonstrated a conceptually new on-surface synthesis route towards the ultra-high anomalous quantum Hall states [42][43][44] , Wigner crystallization [45] and topological insulating transitions [46] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, 2D second-order topological phases have not only 1D edge states but also 0D corner states, [27,28] promising the realization of nanoscale cavities. [9,11] Various invariants, such as the quadrupole moment, [29][30][31][32] Z N Berry phase, [33][34][35] mirror Chern number, [36] nested Wilson loops and polarization, [25,37,38] have been suggested to characterize these new phases. In parallel with these theoretical studies, the higher-order topological phases have been experimentally observed in quantum [39] and classical systems, including microwave circuits, [40] topolectric circuits, [41] acoustic, [42][43][44][45] and photonic systems, [28,[46][47][48] respectively.…”
Section: Introductionmentioning
confidence: 99%